Managing Convergence of Journalisme and Social Media in Indonesia (American Journal of Interdisciplinary Research and Innovation, 2023)
In the era of contemporary media convergence, the interconnection of journalism and social media is inevitable. New media journalism included in the mass media family cannot stand alone without the presence of social media. Therefore, the management of journalism and social media in mass media companies has currently been a given. Without the link between journalism and social media, it is undoubting that the media company is lame, outdated, and on the verge of collapse, because it is abandoned by its readers, audiences and advertisers. The aim of this study is to describe the process of linked journalism in social media in Indonesia, especially in three media groups. Those are Media Group Network, Republika Group, and MNC Group. This study uses qualitative analysis and data collection techniques of observation, interviews, and library study. The results of this study show that the three media groups have differences in managing their journalism and social media. Media Group Network separates all social media under its authority. Republika Group unites all social media under one roof, while MNC Group differentiates in each of its subsidiary groups. This difference has consequences on the number of their followers. Social media under Media Group Network and MNC Group have relatively few followers due to the large number of media subsidiaries under their auspices. On the other hand, the number of the followers of Republika Group is larger because all media subsidiaries are united in one social media platform of Republika Group.